2019
DOI: 10.35940/ijrte.c6832.098319
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Relationship Construction in Domain Ontology Engineering using Semantic and Thematic Graph Generation Process and Convolution Neural Network

Abstract: In recent studies, Ontology construction plays an important role in translating raw text into useful knowledge. The proposed methodology supports efficient retrieval using multidimensional theory and implements integrated data training techniques before enter the trial process. The proposed approach has used the Semantic and Thematic Graph Generation Process to extract useful knowledge, and uses data mining techniques and web solutions to present knowledge as well as improve search speed and information retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Additionally, data mining techniques are used to present knowledge and to demonstrate the accuracy of information retrieval [2].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, data mining techniques are used to present knowledge and to demonstrate the accuracy of information retrieval [2].…”
Section: Introductionmentioning
confidence: 99%
“…Related studies by Wang et al [110], Kim et al [111], and Bangyal et al [112] all used CNN models to classify text. CNNs are multi-layer networks with convolutional and subsampling layers of multiple 2D layers and fully connected hidden layers [113]. In particular, CNN has an input layer that directly receives two-dimensional objects, a feature extraction process done through convolution, and the subsampling layer implemented using multiple fully connected hidden layers as shown in Figure 16.…”
Section: Relation Discovery In Ontology Learning Involves Attribute O...mentioning
confidence: 99%
“…In particular, CNN has an input layer that directly receives two-dimensional objects, a feature extraction process done through convolution, and the subsampling layer implemented using multiple fully connected hidden layers as shown in Figure 16. It is reported that [113], correct hyperparameters setting improves performance during training. For instance, Guruvayur et al [113] developed a 6-step CNN algorithm for the classification of text and explained that, given a batch size of 50, running for 50 epochs, and A convolution operation uses a filter, called w, to create a new feature based on a window of h words in a word vector [114].…”
Section: Relation Discovery In Ontology Learning Involves Attribute O...mentioning
confidence: 99%
See 1 more Smart Citation